Influential Factors of Mother-Infant Skin-to-Skin Contact Based on the Precede-Proceed Model from the Perspective of Midwives in Torbat Heydariyeh Hospitals - Mohadeseh Adeli; Elham Azmoudeh (Mashhad University of Medical Sciences, 2016)
Background & aim: Skin-to-skin contact immediately after birth plays a pivotal role in proper breastfeeding and mother-infant interaction. Despite numerous benefits of mother-infant skin-to-skin contact, this health behavior is not performed by many midwives. This study aimed to evaluate the influential factors for mother-infant skin-to-skin contact based on the Precede-Proceed model from the perspective of midwives in Torbat Heydariyeh hospitals. Methods:This cross-sectional study was conducted on 50 midwives working in hospitals of Torbat Heydariyeh, Iran in 2015. Demographic data of all participants were collected, and Mother-Newborn Skin-to-Skin Contact Questionnaire was also used based on the Precede-Proceed model. Data analysis was performed in SPSS V.16 using descriptive statistics, tables and graphs. Results: In this study, 88.1% of the midwives had positive attitudes towards skin-to-skin contact, and 90.5% had high perceived self-efficacy in performing the procedure. Major obstacles against establishing proper skin-to-skin contact were neonatal diseases and maternal fatigue (83.3%) from the perspective of midwives. Moreover, 87.5% and 90.5% of the midwives emphasized the pivotal role of social support and motivation, respectively in implementing skin-to-skin contact. Also, more than 90% of the midwives considered training programs, service access and adequate facilities to be influential in the proper establishment of skin-to-skin contact. Conclusion: According to the results of this study, the majority of midwives believed that enabling and reinforcing factors had significant effects on the proper establishment of mother-infant skin-to-skin contact. Therefore, it is recommended thateducational interventions be planned for parents, their family members and health care personnel involved in processes of childbirth and infant care. Furthermore, organizational planning and executive procedures should be developed to study the structures and barriers associated with skin-to-skin contact.